Comparative study to assess the maternal and paternal fetal attachment among the expectant mothers and fathers - Kaur, Sarabjit; Mamta, .; Sagar, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Bonding during pregnancy refers to a process through which a pregnant women experiences feelings and emotions for her fetus, interacts with her fetus and develops a maternal identity during pregnancy. The mothers and fathers interact differently with the developing fetus, but evidences for these differences are contradictory. It is important to recognize the factors influencing maternal fetal attachment and paternal fetal attachment because of the effects on future health and development of the infant. Methods: A descriptive (comparative) research design was used to compare the maternal and paternal fetal attachment among 50 couples [Expectant mothers (50) and Expectant fathers (50) =100] selected by convenience sampling technique, who visited ANC OPD of DMC and Hospital, Ludhiana, Punjab. Modified Maternal Fetal Attachment Scale (Mecca S Cranley, 1979) and Modified Paternal Fetal Attachment Scale (Mecca S Cranley, 1979) were used to assess the maternal and paternal fetal attachment by self-report method. Results: Findings revealed that the maternal fetal attachment was higher than the paternal fetal attachment. There was significant difference between maternal and paternal fetal attachment scores (89.76±13.410 vs 80.62±15.494, p=0.002) respectively. The association of maternal fetal attachment was found to be statistically significant with gravida, parity, live babies, planned pregnancy, history of infertility, method of conception and marital relationship (p<0.05) whereas paternal fetal attachment was found to be statistically significant with duration of marriage, number of live children and method of conception (p<0.05). Conclusions: Thus, the study concluded that the maternal fetal attachment was higher than paternal fetal attachment.